PENERAPAN MEDIA RODA PUTAR PROPANESIA UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS 2 DI SD LABSCHOOL UNESA 1 - Annissa Fitrianita Firdayanti; Farida Istianah; Ismawatin; Nura Aprilia Susanti; Elly Indriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This ponder will look at the utilize of the Propanesia turning wheel media (Pancasila Indonesia turning board) to move forward the learning involvement of course II Pancasila understudies at SD Lab School Unesa 1 Surabaya.This ponder could be a classroom action investigate (PTK) utilizing the Kemmis and Taggart demonstrate.The subjects of this think about were Lesson II Lab School Unesa totaling 27 understudies.Test comes about, perception comes about, and reports were utilized as inquire about information.Based on the inquire about information collected, the inquire about comes about were positive with understudy learning results expanding from 48% in Cycle I to 93% of understudies completing Cycle II.In this manner, the learning results of Course II Pancasila subjects can be made strides by utilizing the Propanesia media.